The role of plastic debris in the biogeochemical cycle of mercury in Lake Erie and San Francisco Bay. (October 2021) - Bowman, Katlin L.; Lamborg, Carl H.; Agather, Alison M.; Hammerschmidt, Chad R.
Abstract: The accumulation of plastic debris that concentrates hydrophobic compounds and microbial communities creates the potential for altered aquatic biogeochemical cycles. This study investigated the role of plastic debris in the biogeochemical cycling of mercury in surface waters of the San Francisco Bay, Sacramento River, Lake Erie, and in coastal seawater. Total mercury and monomethylmercury were measured on plastic debris from all study sites. Plastic-bound microbial communities from Lake Erie and San Francisco Bay contained several lineages of known mercury methylating microbes, however the hgcAB gene cluster was not detected using polymerase chain reaction. These plastic-bound microbial communities also contained species that possess the mer operon, and merA genes were detected using polymerase chain reaction. In coastal seawater incubations, rapid mercury methylation percentages were greater in the presence of microplastics and demethylation percentages decreased as monomethylmercury additions adsorbed to microplastics. These findings suggest that plastic pollution has the potential to alter the biogeochemical cycling of mercury in aquatic ecosystems. Graphical abstract: Unlabelled Image Highlights: Monomethylmercury adsorbs to plastic debris in estuarine and freshwater environments. Plastic-bound microbial communities harbor merA genes, which infer mercury resistance. Adsorption of monomethylmercury to microplastics may interfere with natural photodecomposition reactions.